A new species of Eugenia sect. Racemosae (Myrtaceae) from Northeastern Brazil - Moreira, Víctor De Paiva; Cunha, Hercília Freitas Da; Lima, Igor Gonçalves; Proença, Carolyn Elinore Barnes (Phytotaxa, 2025)
This paper presents a description of a new species of Eugenia (Myrtaceae). We also provide a distribution map and a coloured plate with images from live plants and herbarium specimens. Eugenia curupira has been collected in the Atlantic Forest domain and occurs in the coastal sand vegetation known as restinga and in semi-deciduous seasonal forest. It is promptly recognized by the glossy appearance of its leaves when dried and by its reduced raceme. Eugenia curupira is morphologically similar to E. candolleana, from which it differs by its striate bark, raceme with up to four flowers, ferruginous trichomes, shorter pedicels and red fruits. The morphology of the new species suggests its infrageneric placement in Eugenia sect. Racemosae. Eugenia curupira is here categorized as Endangered (EN) according to the IUCN criteria.